Integrated solution for very high cardiovascular risk patients. Rationale and design of a pilot study - E. I. Pavlyuk; M. V. Ionov; A. S. Alieva; N. G. Avdonina; A. N. Yakovlev; N. E. Zvartau (Российский кардиологический журнал)
Coronary artery disease (CAD) is the most common cardiovascular disease and the leading cause of morbidity and mortality. Acute coronary syndrome (ACS) as an abrupt destabilization of CAD, multiplies the risk of cardiovascular events. To reduce the incidence of recurrent cardiovascular events, timely tackling potentially reversible risk factors such as hypertension and/or hyperglycemia is imperative. However, a solid basis for a secondary prevention lies in the treatment of dyslipidemia and begins in the first hours of hospital admission. Despite considerable evidence regarding the efficacy and safety of lipid-lowering therapy, averagely only one third of patients maintain control of lipids. The main challenges are low adherence, poor continuity of medical care, and the lack of an ambulatory routine follow-up. Telehealth solutions are believed to address these barriers and may be considered as an add-on to in-person patient care. Telemonitoring of vital and laboratory parameters, remote patient counseling can be introduced into routine care delivery. Telemedicine shows promise for fostering better clinical effect, and provides health-related quality of life improvement.It is planned to conduct a pilot observational study aimed to create and to test an integrated solution, i.e. telemonitoring and remote counseling in patients of very high cardiovascular risk with ACS followed by myocardial revascularization. The goal is to determine the clinical effectiveness, i.e achievement of target values of blood pressure, lipid profile and glycemia, and patient-centeredness of this approach.